Misure di Biosicurezza nell'Allevamento Avicolo - Angelini, Patrizia (Università di Parma. Dipartimento di Scienze Medico-Veterinarie, 2020)
Biosecurity is a topic of interest in poultry farming. In fact, the entire meat and egg production chain are included in biosecurity programs. The introduction addresses the subject matter: poultry farming, including the most important definitions, the types of breeding and the situation of poultry production in Italy, both in terms of egg production and meat production. It was considered necessary to devote a chapter to the epidemiology of diseases, essential to develop an effective biosecurity plan. In fact, prevention is based on a deep knowledge of diseases in all their aspects. This work also deals with the intervention strategies to be adopted in case of avian infectious disease outbreak, together with the strategies to apply in the specific areas and compartments, as described in the Terrestrial Animal Health Code (TAHC ). The topic of biosecurity is addressed both from a theoretical and practical point of view. First, a definition integrated by several texts is reported, then an overview of the biosecurity program and its cornerstones follows: isolation, cleaning and disinfection, vaccination, eradication and immunogenetic resistance. The thesis illustrates the management of biosecurity in Italian farms, referring even to current legislation at European, national, and regional level. It complies with the regulations of the Lombardy region. Also, the evolution of legislation over years are addressed, closely related to the episodes of avian flu that followed. Biosecurity management is presented through the primary, secondary and tertiary “control zones”; this choice was considered the best from an organizational and practical point of view, because it addresses all the steps, from the single shed to the outside: breeding, complex, etc. The control of livestock biosecurity (AUDIT) is displayed, relating to the official control carried out by the ATS competent for the territory. In conclusion, given the current situation due to SARS-CoV-2, aetiological agent of COVID-19, it was considered appropriate to ...